Report from the STRAND Working Group on the 2019 STR sequence nomenclature meeting. (November 2019) - Gettings, Katherine Butler; Ballard, David; Bodner, Martin; Borsuk, Lisa A.; King, Jonathan L.; Parson, Walther; Phillips, Christopher
Highlights: STR sequence nomenclature meeting hosted by the STRAND Working Group was held in 2019. Attendees included researchers, vendors developing bioinformatic methods, and government representatives. This report summarizes the topics discussed at the meeting. Abstract: This report summarizes topics discussed at the STR sequence nomenclature meeting hosted by the STRAND Working Group in April 2019. Invited attendees for this meeting included researchers known-to-us to be developing STR sequence-based nomenclature schemata, scientific representatives from vendors developing STR sequence bioinformatic methods, DNA intelligence database curators, and academic experts in STR genomics. The goal of this meeting was to provide a forum for individuals developing nomenclature schemata to present and discuss their ideas, encouraging mutual awareness, identification of differences in approaches, opposing aspects, and opportunities for parallelization while some approaches are still under development.